A systematic review of the influence of the retail food environment around schools on obesity-related outcomes - Scarborough, P; Matthews, A; Cowburn, G; Foster, C; Roberts, N; Rayner, M; Williams, J (Blackwell Publishing Ltd, 2014)
The high prevalence of childhood obesity has led to questions about the influence of 'obesogenic' environments on children's health. Public health interventions targeting the retail food environment around schools have been proposed, but it is unclear if they are evidence based. This systematic review investigates associations between food outlets near schools and children's food purchases, consumption and body weight. We conducted a keyword search in 10 databases. Inclusion criteria required papers to be peer reviewed, to measure retailing around schools and to measure obesity-related outcomes among schoolchildren. Thirty papers were included. This review found very little evidence for an effect of the retail food environment surrounding schools on food purchases and consumption, but some evidence of an effect on body weight. Given the general lack of evidence for association with the mediating variables of food purchases and consumption, and the observational nature of the included studies, it is possible that the effect on body weight is a result of residual confounding. Most of the included studies did not consider individual children's journeys through the food environment, suggesting that predominant exposure measures may not account for what individual children actually experience. These findings suggest that future interventions targeting the food environment around schools need careful evaluation. © 2014 International Association for the Study of Obesity.